Sinking particles in the photic zone: relations with biogeochemical properties in different sectors of the Cananéia-Iguape Estuarine-Lagoon Complex (CIELC)-Brazil (Ocean and Coastal Research, 2024)
Over the last decades, regional climate changes, erosion, and heightened agricultural runoffs have increasednutrient and particle input in rivers, unbalancing the biogeochemical cycle of this suspended material alongestuaries. In this context, particle fluxes in the euphotic zone, a very productive layer and important tomaintain the food chain and estuarine preservation, require better understanding. This study aims to evaluateparticle sedimentation fluxes in the photic zone of the Cananéia-Iguape Estuarine-Lagoon Complex (CIELC),considering sectors under different salinities and trophic statuses. A cylindrical sediment trap was installed atthe base of the photic layer to measure particle fluxes and photopigments. Meanwhile, water samples weretaken to measure temperature, salinity, pH, dissolved oxygen, and nutrients. Valo Grande (a freshwater domain)showed high nutrient concentrations, in which high fluxes of phaeopigments and chlorophyll-b highlighted thecontribution of vegetable detritus to particle sinking. In the Batatais mangrove creek, the high fluxes of organicparticles (675.32 mg m-2 d-1) and chlorophyll-a (98.40 mg m-2 d-1) evinced a high contribution of microplanktonto carbon sinking. During the winter of 2018, flocculation processes were evinced in the flood tide of theCananéia Bay as an important driver of sedimentation rates, with considerable fluxes of inorganic particles(1161.20 mg m-2 d-1) and chlorophyll-a (83.27 mg m-2 d-1). In the summer of 2019, we observed a lower flux intotal particles (451.24 mg m-2 d-1) in a period of haline stratification. In the Ararapira Channel, the lowest organicparticle fluxes (<100 mg m-2 d-1) were associated with ultra-oligotrophic conditions, indicating a low influenceof microplankton on sinking particles. These findings suggest that freshwater input, tidal variation, and trophicstatus are relevant controls of sinking particles in different CIELC sectors.